INFLUENCE OF SOCIAL MEDIA PROMOTION, CUSTOMER VALUE, AND PRODUCTDIVERSITY IN EYELASH EXTENTION PURCHASING DECISIONS ON HANLASHES IN GRESIK - Ida Asmaul Laili; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to test and analyze the Effect of Social Media Promotion, Customer Value and Product Diversity on Purchasing Decisions. This research carried out at Hanlashes Customers in Gresik. With a sample size of 100 respondents collected using a questionnaire. This research uses an approach quantitative. The sampling technique in this research uses the Lemeshow formula, Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis, Hypothetical Test (ttest), and Simultaneous Test (f test) with SPSS 29.